Policy Change and Implementation of New Village Regulation Based on Public Administration Perspective - Ike Wanusmawatie; Bambang Supriyono; Luqman Hakim; MR Khairul Muluk (e-2477-1929)
The purpose of this study is to analyze the policy change of village regulation and the implementation of Law No 6/2014 on the Village as new village policy. The method of this research was qualitative. It was conduct in two locations, i.e: Kairane village of Kupang Regency and Dringu village of Probolinggo Regency. The result indicates that although the policies used are the same, but they produce different outputs. In isolated villages, the dominant output is village infrastructure. This is due to inadequate water and transportation facilities. Whereas in the developed villages, there are more administrative services. Thus village funds are difficult to absorb in infrastructure activities, but disbursed for village apparatus honorarium fees. On the other hand, policy change is more on political process and always do when village government ineffective. In conclusion, the implementation of village policy in Indonesia has different results. Let’s focus on managerial approach to make policy robust not only political: the advanced village focus on better public services, while the isolated focus on village development.